MODELLING SMEs’ BEHAVIORAL INTENTION TO ADOPT ISLAMIC CROWDFUNDING-SMALL AND MEDIUM ENTERPRISES (ICSMEs) MODEL AS A SOURCE OF FINANCING IN MALAYSIA - Mohd Thas Thaker, Mohamed Asmy Bin (Journal of Islamic Monetary Economics and Finance, 2018)
The present study has proposed Islamic Crowdfunding-Small and Medium Enterprises (ICSMEs) model to assist SMEs in meeting their need to access external financial services in Malaysia. Upon the proposed model, this study examines the behavioural intention of SMEs to use ICSMEs model. The primary data are collected from the survey administered to SMEs in the Klang Valley (n=250) and the analysis is conducted using Partial Least Squares (SmartPLS). Furthermore, the model has been validated its acceptance in the field by adopting the Technology Acceptance Model (TAM). This study has revealed that both the perceived usefulness and perceived easy to use are found to have a positive impact on the behavioral intention of SMEs to use ICSMEs model, which later assist them to access to financial services in Malaysia. Furthermore, perceived easy to use has a positive relationship and direct effect with perceived usefulness of SMEs to use the ICSMEs model. The findings of this study can be used to develop a specific framework in which to examine other components of using the ICSMEs model’s behavior and to plan appropriate intervention strategies to increase financial accessibility by SMEs.